1985
DOI: 10.1111/j.1365-246x.1985.tb05148.x
|View full text |Cite
|
Sign up to set email alerts
|

Source process and tectonic implications of the great 1975 North Atlantic earthquake

Abstract: Summary. The Atlantic segment of the Africa–Europe plate boundary has usually been interpreted as a transform boundary on the basis of the bathymetric expression of the Gloria fault and dextral strike‐slip first‐motion mechanisms aligned along the Azores–Gibraltar line of seismicity. The 1975 May 26 earthquake (Ms=7.9) was assumed to fit into this framework because it occurred in the general area of this line and has a similar first‐motion focal mechanism (strike=288°, dip=72°, slip angle=184°). However, seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 25 publications
0
45
0
Order By: Relevance
“…These events not only follow the Gloria Fault itself but also a second source zone also striking almost EW, ca. 200 km south (Lynnes and Ruff, 1985). This can correspond to either the development of a tectonic block or the re-activation of a previous transform domain (Kaabouben et al, 2008).…”
Section: Tsunamigenic Source Areasmentioning
confidence: 99%
“…These events not only follow the Gloria Fault itself but also a second source zone also striking almost EW, ca. 200 km south (Lynnes and Ruff, 1985). This can correspond to either the development of a tectonic block or the re-activation of a previous transform domain (Kaabouben et al, 2008).…”
Section: Tsunamigenic Source Areasmentioning
confidence: 99%
“…Both observation and theory showed that this is not the case. The North Atlantic earthquake of 1975, a strike-slip event, generated observable tsunamis [Lynnes and Ruff, 1985]. Tsunamis were also recorded from the 1906 San Francisco earthquake.…”
Section: Tsunami Generationmentioning
confidence: 99%
“…Antunes (1944) presented the first epicentre location, using only data from the Portuguese seismic network, at −18.9 • E, 38.7 • N. Gutenberg and Richter (1949) relocated the epicentre at −18.5 • E, 37.50 • N and computed the earthquake magnitude as M s = 8.2. Later, Lynnes and Ruff (1985), using a master-event technique relative to a better characterized event (26 May 1975), relocated the epicentre at −19.1 • E, 37.6 • N. Udias et al (1976) computed the earthquake magnitude as 8.3.…”
Section: The 25 November 1941 Earthquakementioning
confidence: 99%
“…The predominant focal mechanism is strike-slip (Buforn et al, 1998(Buforn et al, , 2004Argus et al, 1989). Among these events are those that occurred on 25 November 1941 (Udias et al, 1976;Lynnes and Ruff, 1985), 9 June 1969 (Argus et al, 1989), 26 May 1975(Buforn et al, 1998Argus et al, 1989;Kaabouben et al, 2008) and 17 October 1983 (Argus et al, 1989). Some of these earthquakes generated tsunamis, described in historical documents and recorded by tide stations, namely on 31 March 1761, 25 November 1941and 26 May 1975(Baptista et al, 2006Kaabouben et al, 2008;Baptista and Miranda, 2009).…”
Section: Introductionmentioning
confidence: 99%